2011
DOI: 10.2114/jpa2.30.23
|View full text |Cite
|
Sign up to set email alerts
|

Change in PGC-1α Expression in Rat Skeletal Muscle after Low-intensity Prolonged Swimming Exercise

Abstract: After 6-h low-intensity swimming exercise (LIE), peroxisome proliferator-activated receptor g coactivator -1a (PGC-1a) in whole and nuclear fractions in rat skeletal muscle was higher than the control rats' muscles up to 18 h after LIE. However, no study has reported change in PGC-1a content after that. Therefore, we measured PGC-1a in whole and nuclear fractions in rat skeletal muscle up to 24 h after LIE. Furthermore, we evaluated change in the mRNA of daminolevulinate synthase (ALAS), a mitochondrial protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Thus, according to the literature a single bout of exercise can activate calcium/calmodulin-dependent protein kinase (CaMK), p38 mitogen-activated protein kinase (p38 MAPK), cyclic adenosine monophosphate (cAMP), and phosphorylate AMP activated protein kinase (AMPK), which are the molecular signals responsible for the increase in PGC-1 α expression ( Bonen, 2009 ; Lira et al, 2010 ; Perry and Hawley, 2018 ; Memme et al, 2021 ). Our results are in accordance with the literature and demonstrate that a single bout of exercise increases the expression and/or content of PGC-1 α ( Wright et al, 2007 ; Ikeda et al, 2008 ; Seebacher and Glanville, 2010 ; Fujimoto et al, 2011 ; Shute et al, 2018 ) and NRF-1 ( Murakami et al, 1998 ; Seebacher and Glanville, 2010 ; Daussin et al, 2012 ). More importantly, our main finding is that melatonin potentiates the up-regulation of PGC-1 α expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, according to the literature a single bout of exercise can activate calcium/calmodulin-dependent protein kinase (CaMK), p38 mitogen-activated protein kinase (p38 MAPK), cyclic adenosine monophosphate (cAMP), and phosphorylate AMP activated protein kinase (AMPK), which are the molecular signals responsible for the increase in PGC-1 α expression ( Bonen, 2009 ; Lira et al, 2010 ; Perry and Hawley, 2018 ; Memme et al, 2021 ). Our results are in accordance with the literature and demonstrate that a single bout of exercise increases the expression and/or content of PGC-1 α ( Wright et al, 2007 ; Ikeda et al, 2008 ; Seebacher and Glanville, 2010 ; Fujimoto et al, 2011 ; Shute et al, 2018 ) and NRF-1 ( Murakami et al, 1998 ; Seebacher and Glanville, 2010 ; Daussin et al, 2012 ). More importantly, our main finding is that melatonin potentiates the up-regulation of PGC-1 α expression.…”
Section: Discussionsupporting
confidence: 93%
“…However, in an opposite scenario of high PGC-1 α , there are evidences showing a lower endurance performance in skeletal muscle-specific PGC-1 α knockout (PGC-1 α MKO) ( Handschin et al, 2007 ) and whole-body PGC-1 α knockout animals (PGC-1 α KO) ( Leone et al, 2005 ). Although it is well established that a single bout of exercise is able to increase content and/or expression of PGC-1 α ( Wright et al, 2007 ; Ikeda et al, 2008 ; Seebacher and Glanville, 2010 ; Fujimoto et al, 2011 ; Shute et al, 2018 ) and NRF-1 ( Murakami et al, 1998 ; Seebacher and Glanville, 2010 ; Daussin et al, 2012 ), reports on these proteins after exercise until exhaustion are lacking for animals treated with melatonin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a mouse study conducted by Pang et al has reported that PGC-1α expression increased during 30 min of treadmill exercise but decreased during 1 h of treadmill exercise, suggesting that the regulation of gene and protein expression may differ according to the duration of exercise [11]. A few studies suggested 6-h prolonged acute bout of swimming exercise-induced an elevated mRNA expression of PGC-1 immediately after [21]and elevation of PGC-1α protein was maintained 18 and 24 h after the exercise in rat epitrochlearis muscle [22]. Given these previous findings, the expression of PGC-1α is considered to occur when some time has passed after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been suggested in animal studies that low intensity exercise can activate PGC-1α [ 62 , 63 ] independently of 5′ adenosine monophosphate-activated protein kinase (AMPK) activation, which might only occur with exercise of higher intensity [ 64 ].…”
Section: Discussionmentioning
confidence: 99%